Nifedipin versus magnesium sulfate for suppression of preterm labor: A randomized Clinical trial - Sedigheh Esmaeilzadeh; Mahbobe Ramezani; Zeinab Pahlevan; Sina Taheri; Faezeh Zabihi; Mojgan Naeimirad (Babol University of Medical Sciences, 2017)
Background: Preterm labor is a leading cause of fetal and neonatal morbidity and mortality. There are various kinds of drugs used to suppress the preterm labor, but they are not thoroughly effective. The aim of this study was to compare the effectiveness of oral nifedipine with intravenous magnesium sulfate in delaying the preterm labor. Methods: A randomized, clinical trial was conducted in a hospital in Babol, Iran. One hundred twenty singleton pregnant women with preterm labor, 24-37 weeks of gestation, were randomly assigned to receive oral nifedipine or intravenous magnesium sulfate. The main outcome of the study was the inhibition of uterine and the secondary outcome was the side effect related to drugs and neonatal outcome. The data were analyzed with SPSS software, using chi-squared test and independent t test. Results: According to the results, in 35% of women in the nifedipine group and 23.3% of women in the magnesium sulfate group, the inhibited uterine contraction was less than 48 hours. Also, in 65.0% of women in the nifedipine group and 76.7% of women in the magnesium sulfate group, the inhibited uterine contraction was more than 48 hours. There was no significant difference between the nifedipine and the magnesium sulfate groups in the inhibition of uterine contraction in both less and more than 48 hours. The total side effects of medication were found to be lower in patients receiving oral nifedipine than those who received intravenous magnesium sulfate. (26.6 vs. 45.0) (p= 0.036). There was no significant difference in neonatal outcome between the two groups. Conclusion: Oral nifedipine should be a suitable alternative to intravenous magnesium sulfate in suppression preterm labor with fewer side effects.